Analys av blågröna lösningars effekt på översvämning: GIS-baserad hydrologisk modellering av pluvial översvämning i Trelleborg - Persson,Airen (2026)
As a result of global warming, the hydrological cycle is expected to intensify. With this follows an increase in precipitation, which is predicted to cause a growing frequency and level of pluvial flooding. Urban settlements will likely be affected the most, and with the continuing growth of cities, more people will be at risk of endangerment. Thus, it is of immense importance for cities to strengthen their resilience against pluvial flooding. [i]Blue-Green solutions[/i], or [i]Blue-Green infrastructure (BGI)[/i], describe multifunctional measures with limited or no technological infrastructure, which uses ecosystem functions to create several benefits, such as providing recreational space, reducing greenhouse gas emissions, and mitigating flooding. In this paper, the planning area of Övre and Stadsparkskvarteren in the Swedish city of Trelleborg is used as a case study to examine how implementation of BGI can affect pluvial flooding. This paper studies the mitigation effect of BGI by using ArcGIS Pro and PluvioFlow to simulate: (1) how much flooding the planning area is risking; (2) how suggested solutions affect flood distribution, water depth level and water volume in the planning area; and (3) how large an area of BGI would be required to mitigate all flooding. The result of the study shows that Övre and Stadsparkskvarteren will face great consequences during different types of rainfall events, while large concentrations of water will arise in several areas. After implementation of BGI, the water volume increases in the BGI areas due to accumulation, while areas without BGI have either an increase or decrease. For the planning area to manage a 100-year rainfall event, a BGI area of almost 27 % of the whole planning area is needed. In summary, the study shows a need for Trelleborg to perform further studies of how to increase resilience against pluvial flooding.
Keywords: Environmental science; Flooding; Pluvial Flooding; Precipitation; Blue-Green Solutions; Blue-Green Infrastructure (BGI); Urban Planning; Geographical Information System (GIS); Resilience; Mitigation strategies